Characteristics and catalytic activity of Pd-Cu/SiO2 synthesized by sol-gel method for the hydrodechlorination of tetrachloroethylene. - Lien, Nguyen Hồng; Nam, Chu Thi Hai (Vietnam Journal of Chemistry, 2012)
The double metallic catalyst Pd-Cu/SiO2 was synthesized using sol-gel method with various ratios of Pd/Cu and characterized for their physico-chemical properties. Their catalytic activities were also tested for the hydrodechlorination of tetrachloroethylene, one of the most popular solvents used in different industries. Better tetrachloroethylene conversion over double metallic samples compared to the single ones indicated the advantage of these materials in keeping the active sites out of deactivation.